Pharmacokinetics and Tolerability of the Novel Oral Prostacyclin IP Receptor Agonist Selexipag - Kaufmann, Priska (Am J Cardiovasc Drugs, 2015)
PURPOSE: Targeting the prostacyclin pathway is an effective treatment option for pulmonary arterial hypertension (PAH). Patients with PAH have a deficiency of prostacyclin and prostacyclin synthase. Selexipag is an orally available and selective prostacyclin receptor (IP receptor) agonist. Selexipag is hydrolyzed to its active metabolite ACT-333679, also a selective and potent agonist at the IP receptor. METHODS: In this phase I study the pharmacokinetics (PK) and tolerability of single and multiple ascending doses of selexipag were investigated in a double-blind, placebo-controlled manner in 64 healthy male subjects. An additional group of 12 subjects received an open-label dose of selexipag 400 μg in the fasted condition and after a meal. RESULTS: Maximum plasma concentrations of selexipag and ACT-333679 were reached within 2.5 and 4 h, respectively, with mean half-lives of 0.7–2.3 and 9.4–14.22 h. In the presence of food, exposure to ACT-333679 was decreased by 27 %. The most frequent adverse event was headache. Selexipag was well tolerated up to a single dose of 400 μg and multiple doses of 600 μg following an up-titration step. No relevant treatment-related effects on vital signs, clinical laboratory, and electrocardiogram (ECG) parameters were detected. CONCLUSION: Selexipag exhibits a good tolerability profile and PK properties that warrant further investigation.